A perceptive individual time trial performed by triathletes to estimate the anaerobic threshold. A preliminary study - Groslambert, A.; Grappe, F.; Bertucci, W.; Perrey, S.; Girard, A. J.; Rouillon, J. D. (The Journal of Sports Medicine and Physical Fitness, 2004)
AIM: The aim of the study was to test the ability to estimate the power output (PO) and heart rate (HR) associated with ''anaerobic threshold'' levels for triathletes by means of a 30-min perceptive individual time trial (PITT30). METHODS: Thirteen triathletes (8 males and 5 females) performed an incremental exercise test to estimate maximal parameters such as oxygen uptake, power output and heart rate. From this incremental exercise test, the individual anaerobic threshold (IAT) and ventilatory threshold (VT) for all subjects were estimated. Then, the subjects completed a PITT30 at self-selected work intensity on a stationary ergometer equipped with the SRM Training System. Mean values of PO, HR, and pedalling cadence were recorded continuously between the 5th and the 30th min of the test. RESULTS: Significant correlations were observed between the mean PO recorded during PITT30 and PO measured at IAT (r=0.88; p<0.0001) and at VT (r=0.89; p<0.0001). Furthermore, bias and limits of agreement confirm the degree of association between the 3 METHODS: However, PITT30 over-estimated HR values compared to the values obtained at IAT and VT. CONCLUSION: It was concluded that, for triathletes, mean PO measured with PITT30 allows a partial valid estimation of PO associated with 2 known methods of ''anaerobic threshold'' determination. The application of PITT30 may offer a useful tool for athletes and coaches to estimate the ''anaerobic threshold'' in order to control accurately the training effects.